Sistem Informasi Manajemen Proyek Berbasis Website Pada PT XYZ - Rizani Teguh (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2019)
Project management is a project processing process that includes planning, organizing and managing resource tasks to realize the goals to be achieved, taking into account time and cost factors. PT. Ahaz Karya Mandiri is a project contractor company engaged in the development of building design. To support the performance of human resources in the company, an information system is needed that can control project progress and process data accurately, in fact the existing system is inadequate. Sofrom this research is intended to create a project management information system that has been computerized and the data has been integrated. The methodology used is iterative methodology (Iterative). In the analysis phase use PIECES analysis, Usecase Diagram, and Rich Picture. At the design stage used Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD). Application development uses MySQL for the database and Website to support system development and several other languages ​​such as PHP, and others. The results of the research are in the form of project management information systems that have met the needs of PT. Ahaz Karya Mandiri, including the features of contract submission, project development, reporting and project documentation.